Petroleum geochemistry, burial history and shale gas potential of the Goldwyer Formation - Canning Basin, Western Australia - Torghabeh, A.K.; Rezaee, Reza; Pimentel, N.; Johnson, Lukman; Alshakhs, Munther (INDERSCIENCE ENTERPRISES LTD, 2019)
Several organic-rich shale horizons in the Canning Basin, Western Australia, acted as source rocks for conventional oil and gas fields. The aim of this study is to investigate one of its units, the Goldwyer Formation (Ordovician in age, as the Utica Shale in USA) as a potential shale gas play. Geochemical analysis such as Rock-Eval pyrolysis and total organic carbon (TOC) estimation, as well as thermal and burial history modelling were used. The organic matter is mixed type II/III kerogen and the total organic carbon (TOC) values range between 0.16 and 4.8 wt%. Tmax values between 335°C and 471°C and vitrinite reflectance values between 0.71 and 1.3 Ro% point to the main oil to wet and dry thermogenic gas zones, with a trend of increasing maturity in the west-central part of the basin. The results of this study show that the Goldwyer shale may be considered as potential shale-gas play.